2010
DOI: 10.1111/j.1471-0528.2010.02735.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduced placental prolyl hydroxylase 3 mRNA expression in pregnancies affected by fetal growth restriction

Abstract: Objective To investigate the role of the hypoxia-inducible factor (HIF) pathway in fetal growth restriction (FGR).Design A case-control study.Setting Research laboratory and gynaecology clinic.Sample Twenty placentas from normal pregnancies and 20 from FGR pregnancies.Methods RNA extraction, cDNA synthesis, quantitative real-time polymerase chain reaction (qRT-PCR) assay, statistical analysis.Main outcome measures mRNA expression of HIF-1a, HIF-2a and HIF-b (ARNT), along with prolyl hydroxylase domain 3 (PHD3)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 42 publications
2
6
0
1
Order By: Relevance
“…Statistical analysis revealed that PE-affected pregnancies with BWC<5 had increased DLL3 mRNA and NICD3 protein levels compared with PE-affected pregnancies with BWC>5. This observation is similar to one in our previous study on pregnancies complicated by FGR, in which PHD3 , a member of the HIF hypoxia pathway, was higher in babies born from FGR pregnancies with BWC<0.5 compared to babies born from FGR pregnancies with BWC>0.5 [ 19 ]. Additionally, in women with PE that were on their first parity, HEY2 transcript levels were increased compared with PE women that gave birth to their 2 nd or 3 rd child.…”
Section: Discussionsupporting
confidence: 90%
“…Statistical analysis revealed that PE-affected pregnancies with BWC<5 had increased DLL3 mRNA and NICD3 protein levels compared with PE-affected pregnancies with BWC>5. This observation is similar to one in our previous study on pregnancies complicated by FGR, in which PHD3 , a member of the HIF hypoxia pathway, was higher in babies born from FGR pregnancies with BWC<0.5 compared to babies born from FGR pregnancies with BWC>0.5 [ 19 ]. Additionally, in women with PE that were on their first parity, HEY2 transcript levels were increased compared with PE women that gave birth to their 2 nd or 3 rd child.…”
Section: Discussionsupporting
confidence: 90%
“…The observed down-regulation in YD embryos of egln2 and egln3 (regulators of hypoxia-inducible factors (Hifs) [ 23 ] and also known as phd1 and phd3 [ 24 ]) at 32 hpf and 24/48 hpf respectively, complies with hypoxia signaling in YD embryos ( egln3 has been validated by qRT PCR, Additional file 6 , see Additional file 2 for DE values). Egln3 down-regulation in YD embryos is reminiscent with down-regulation of its human orthologue in placenta from fetal growth restricted (FGR) children [ 25 ]. Hypoxia signaling has also been observed in fetal murine hearts and brains from undernourished mothers [ 26 , 27 ] and is consistent with pronounced oxidative stress in small-for-gestational age (SGA) newborns from undernourished mothers [ 9 ].…”
Section: Resultsmentioning
confidence: 99%
“…Total RNA was extracted using TRIzol as described previously [36,37]. Placental tissues were cut into small sections and homogenized in the presence of 1 ml TRIzol.…”
Section: Rna Extractionmentioning
confidence: 99%